Quality with underlying epistemological criteria - Caballero, Romina; Simeoni, Irene Amelia; Lepez, Carlos Oscar (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Introduction: the fact that a term is freely used and decoded according to the nature in which it is intended to be applied or towards the semiotic sense that the reader assigns to it implies a review of the various ways in which it is interpreted and to the origin of the concept of quality, and it is often observed that the concept of quality is given a partial and not integral content. The objective of the work is directed to the theoretical description of quality in health, detailing concepts, characteristics and application.Methods: qualitative, narrative and exploratory study based on literature review.Development: quality of care is the set of technical-scientific, material and human characteristics that the health care provided to beneficiaries must have, in order to achieve the possible effects that will result in the greatest number of healthy years of life and a cost that is socially and economically viable for the system and its members. Its characteristics are timeliness, agility, accessibility, continuity, sufficiency, safety, comprehensiveness and integrity, logical-scientific rationality, cost-effectiveness, efficiency, humanity, information, transparency, consent and degree of user satisfaction; in a technical and applied sense, several models have been used in quality evaluation, among which the pioneer Donabedian stands out, who developed a model based on three areas: structure, process and results; Galán developed another model focused on the evaluation of the attributes of quality: care, demand, supply, process, results and impact.Conclusions: quality in Health is made up of a set of values, principles, policies and action strategies aimed at promoting change and improvement activities in the organization, in order to obtain the greatest satisfaction of the staff and the patient; and it must be defined, planned, programmed, its real cost determined, evaluated and, fundamentally, led by the management teams.